A comparison of practical assessment methods to determine treadmill, cycle, and elliptical ergometer VO2peak - Mays, R. J; Boer, N. F.; Mealey, L. M; Kim, K. H.; Goss, F. L. (The Journal of Strength and Conditioning Research, 2010)
This investigation compared estimated and predicted peak oxygen consumption (VO2peak) and maximal heart rate (HRmax) among the treadmill, cycle ergometer, and elliptical ergometer. Seventeen women (mean ± SE: 21.9 ± 0.3 y) exercised to exhaustion on all modalities. American College of Sports Medicine metabolic equations were used to estimate VO2peak. Digital displays on the elliptical ergometer were used to estimate VO2peak. Two individual linear regression methods were used to predict VO2peak: (a) 2 steady state heart rate (HR) responses up to 85% of age-predicted HRmax and (b) multiple steady state/nonsteady state HR responses up to 85% of age-predicted HRmax. Estimated VO2peak for the treadmill (46.3 ± 1.3 ml/kg·min) and the elliptical ergometer (44.4 ± 1.0 ml/kg·min) did not differ. The cycle ergometer estimated VO2peak (36.5 ± 1.0 ml/kg·min) was lower (p < 0.001) than the estimated VO2peak values for the treadmill and elliptical ergometer. Elliptical ergometer VO2peak predicted from steady-state (51.4 ± .8 ml/kg·min) and steady-state/nonsteady-state (50.3 ± 2.0 ml/kg·min) models were higher than estimated elliptical ergometer VO2peak, p < 0.01. HRmax, and estimates of VO2peak were similar between the treadmill and elliptical ergometer; thus, crossmodal exercise prescriptions may be generated. The use of digital display estimates of submaximal oxygen uptake for the elliptical ergometer may not be an accurate method for predicting VO2peak. Health-fitness professionals should use caution when utilizing submaximal elliptical ergometer digital display estimates to predict VO2peak.